Correlation Between Maternal TNF-α Levels and Neonatal Outcomes in Obese Pregnant Women with Term Pregnancy - Azzahra Azzahra; Yusrawati Yusrawati; Husnil Kadri; Aladin Aladin; Almurdi Almurdi (Cell and BioPharmaceutical Institute, 2026)
Background: Maternal obesity causes chronic low-grade inflammation with elevated TNF-α, potentially disrupting the intrauterine environment and fetal development. Previous studies have primarily focused on preterm inflammation or cytokine levels earlier in pregnancy. However, data on the relationship between maternal TNF-α levels at term pregnancy and immediate neonatal outcomes in obese women remains limited, especially in the Indonesian population. This study evaluates their correlation in term obese pregnancies.Materials and methods: Maternal serum TNF-α levels were assessed in obese pregnant women with gestational age ≥37 weeks. Blood samples were collected during the third trimester of pregnancy and analyzed using ELISA. Neonatal outcome data were extracted from medical records and evaluated within the first 24 hours of life. Pearson correlation was applied to parametric variables, including maternal TNF-α levels and birth length, while Spearman correlation was used for non-parametric neonatal outcome variables. This cross-sectional study analyzed secondary data from a parent cohort.Results: Maternal TNF-α levels were not significantly associated with neonatal outcomes (all p>0.05). Pearson correlation analysis showed a weak association with birth length (r = 0.214). In contrast, Spearman correlation analyses demonstrated weak or negligible associations with birth weight (ρ = 0.227), head circumference (ρ = 0.043), APGAR score at 1 minute (ρ = −0.100), and at 5 minutes (ρ = −0.014).Conclusion: Maternal TNF-α levels were not significantly associated with neonatal outcomes among obese women with term pregnancies. Assessment of inflammatory status limited to the late third trimester may be inadequate to fully evaluate this relationship, indicating the need for future studies with inflammatory measurements initiated earlier in pregnancy. Keywords: TNF-α, maternal obesity, neonatal outcomes, APGAR score, term pregnancy